Pengolahan Kotoran Sapi Sebagai Bahan Pembuatan Biogas di Kandang Komunal Dusun Sukunan Kelurahan Banyuraden Kecamatan Gamping Sleman Yogyakarta - Handi Trianto; Dodit Ardiatma (Prosiding Sains dan Teknologi, 2022)
Among the many issues related to the environment, there are two issues that are currently developing, namely organic fertilizers and the use of organic waste. It is still widely understood that environmental management is still a burden that only wastes the budget. As technology develops, environmental management makes it possible to make profit no longer a burden. Such as the management of organic waste feces, livestock manure, food waste and other organic waste which is processed into biogas and by-product fertilizers in the form of solid fertilizers, liquid fertilizers and even electrical energy. In the Yogyakarta area, there is an environmental tourism village, to be precise, Sukunan Hamlet, Bayuraden Village, Gamping Sleman District, in this area there is a program for raising cows in shared cages where the amount of waste that interferes with health and environmental aesthetics is converted into raw material for making biogas. The management of the cage together had the idea of ​​​​processing biogas from the waste produced by making a biodigerster, from the utilization of biogas, methane gas was produced which can be used directly as fuel in cooking. Methane gas from the biogas process is channeled through pipes connected to a modified gas stove that is adapted to the use of biogas. Cow dung into biogas as an alternative energy creates added value from cow dung in addition to being compost and makes it easier for people to get energy sources, research objectives, methods used and main conclusions from the article. Keywords: Cow Manure, Biogas, Organic, Fertilizer